2006
DOI: 10.1300/j079v32n04_07
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Child Protective Services Decision-Making Context with Implications for Decision Support System Design

Abstract: The general perception of Child Protective Services (CPS) decision making is that it is inconsistent and prone to error. As a result, risk assessment instruments were developed to enable investigators to make better decisions. The present study uses a qualitative approach with an explicit theoretical framework pertinent to management information systems and decision support system design to examine the context in which investigators operate and make decisions. The resulting information can be used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Additionally, in line with the knowledge-based view of the organization [72][73][74], our study recognizes the important role of knowledge in social work centers as potentially the primary source influencing their functioning. A paradigm shift towards a knowledge-based view of the organization is also suggested by some social work researchers [75,76]. We also aim to contribute the previously neglected aspect of sustainable development, the social dimension of sustainability [5,6].…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, in line with the knowledge-based view of the organization [72][73][74], our study recognizes the important role of knowledge in social work centers as potentially the primary source influencing their functioning. A paradigm shift towards a knowledge-based view of the organization is also suggested by some social work researchers [75,76]. We also aim to contribute the previously neglected aspect of sustainable development, the social dimension of sustainability [5,6].…”
Section: Introductionmentioning
confidence: 90%
“…() explored the potential of what they refer to as ‘artificial intelligence’ to develop ‘expert systems’ to support professional decision‐making. Research‐based development of DSS continued in the 21 st century and identified particular challenges in their design and implementation such as making them useful in the contexts in which they are implemented (Fitch, , ; Foster and Stiffman, ), getting practitioners to use them (Fitch, , ; Foster and Stiffman, ) and accounting for the importance of emotion and bias in human decision‐making (MacFadden and Schoech, ).…”
mentioning
confidence: 99%
“…Using six examples from North America, Europe and Australasia, this article provides an overview and critical appraisal of current developments. It is also important that social workers are aware of these developments and can engage in both debate about DSS and development processes (Fitch, , ). One aim of the article is therefore to inform social workers and stimulate debate within the profession.…”
mentioning
confidence: 99%
“…Workers suggested that incorporating their comments, knowledge and experiences into the agency descriptions and making that knowledge available to other users would facilitate IMPROVE’s use (see Fitch, 2006). Having the knowledge of coworkers embedded in the application would, in their words, “be real helpful” and make it more useful as a first order intervention tool.…”
Section: Discussionmentioning
confidence: 99%